Direct solution of second-order BVPs by homotopy-perturbation method - Abdulaziz.O; Chowdhury .M.S.H; Hashim .I; Momani .S (Universiti Kebangsaan Malaysia, 2009)
In this paper, systems of second-order boundary value problems (BVPs) are considered. The applicability of the homotopy-perturbation method (HPM) was extended to obtain exact solutions of the BVPs directly.